Lasang Lasallian - Carandang, Ernesto V. (Ernesto Villaluz); Sison-Buban, Rakki E.; Delarmente, Leticia O.; De La Salle University (Quezon City Central Book Supply, Inc. for De La Salle University, 2011)
Filipino food offered by canteens located surrounding De La Salle University in the Philippines.
"A centennial publication of De La Salle University"--Verso of title page.
In Tagalog, and some articles in English.
Keywords: De La Salle University; Cooking, Philippine; Formulas, recipes, etc. -- Philippines